Co3O4 Supraparticle‐Based Bubble Nanofiber and Bubble Nanosheet with Remarkable Electrochemical Performance. Issue 12 (15th April 2019) - Huang, Jun; Xiao, Yingbo; Peng, Zhongyou; Xu, Yazhou; Li, Longbin; Tan, Licheng; Yuan, Kai; Chen, Yiwang
Abstract: Hollow nanostructures based on transition metal oxides (TMOs) with high surface‐to‐volumetric ratio, low density, and high loading capacity have received great attention for energy‐related applications. However, the controllable fabrication of hybrid TMO‐based hollow nanostructures in a simple and scalable manner remains challenging. Herein, a simple and scalable strategy is used to prepare hierarchical carbon nanofiber (CNF)‐based bubble‐nanofiber‐structured and reduced graphene oxide (RGO)‐based bubble‐nanosheet‐structured Co3 O4 hollow supraparticle (HSP) composites (denoted as CNF/HSP‐Co3 O4 and RGO/HSP‐Co3 O4, respectively) by solution self‐assembly of ultrasmall Co3 O4 nanoparticles (NPs) assisting with polydopamine (PDA) modification. It is proved that the electrochemical performance of Co3 O4 NPs can be greatly enhanced by the rationally designed nanostructure of bubble‐like supraparticles combined with carbon materials as excellent electrodes for supercapacitors. The favorable structure and composition endow the hybrid electrode with high specific capacitance (1435 F g −1 /1360 F g −1 at 1 A g −1 /5 mV s −1 ) as well as fantastic rate capability. The asymmetric supercapacitors achieve an excellent maximum energy density of 51 W h kg −1 and superb electrochemical stability (92.3% retention after 10 000 cycles). This work suggests that the rational design of electrode materials with bubble‐like superstructures provides an opportunity for achieving high‐performance electrode materials for advanced energy storage devices. Abstract : Hierarchical bubble‐nanofiber‐structured and bubble‐nanosheet‐structured Co3 O4 supraparticle composites are synthesized. The favorable structure and composition endow the hybrid electrode a high utilization rate of active material and shortened transport length for fast ion/electron transport. Thus, the as‐fabricated electrodes show high specific capacitance, superior rate performance, and cycling stability, outperforming most reported Co3 O4 ‐based electrodes.